The Effect of Maltodextrin Concentration and Spray Dryer Drying Temperature on the Characteristics of Coconut Milk Powder - Fitria Yulistiani; Alifia Nuraeni; Sheilla Aulia Sofiatul Mardiah; Irwan Hidayatulloh; Lidya Elizabeth; Nurcahyo (Department of Chemical Engineering, Politeknik Negeri Bandung, 2023)
Coconut milk has a higher water content than other contents, so microbes can easily damage and spoil it. To obtain a low-moisture powder product, the liquid coconut milk was dried using a Buchi Mini Spray dryer B-290 with inlet temperatures of 150°C, 160°C, and 170°C. The researchers added maltodextrin to coconut milk, which had a ratio of grated coconut to the water of 1:3, in concentrations of 9%, 10%, 11%, 12%, and 13%. The addition of maltodextrin and the use of drying temperature did not significantly affect the pH, solubility, and percentage of product mass but did significantly affect the moisture content. The best operating conditions for producing coconut milk powder were at a maltodextrin concentration of 13% and a temperature of 170°C. Under these conditions, the produced coconut milk powder had a pH value of 6.12, a moisture content of 4.56%, a solubility of 98.74%, a product mass of 24.99 grams and an overall percentage of product mass of 21.32%.